The Influence of the Raskin Program on the Welfare of Poor Families in Pagadungan Village, Karangtanjung District, Pandeglang Regency - Adnan, Hasyim; Lisa Agustina (Future Science, 2024)
Rice for the Poor (Raskin) is a government programme to help the poor and food insecure so that they can get cheap rice for their household needs. Problems were found related to this programme policy where the implementation of Raskin rice distribution was still uneven and there was no balance between the Raskin quota and Raskin rice recipients, the number of Raskin received was less than the number of RTMs, the Pagadungan Village Raskin payment was delayed, the Raskin distribution mechanism was long and convoluted sometimes and the quality of Raskin received by RTMs in Pagadungan Village was not in accordance with Bulog's quality standards. Based on this problem, the researcher formulates the main problem in this study, namely How does the Raskin programme affect the welfare of poor families in Pagadungan Village, Karangtanjung District, Pandeglang Regency? With the aim to find out how and how strong the influence of Raskin programme on the welfare of poor families in Pagadungan Village, Karangtanjung Sub-district, Pandeglang Regency. The research was conducted in the first semester of fiscal year 2024 by using descriptive quantitative research approach and method, with the target population oriented research of 497 people and random sample of 83 people. Data collection techniques were carried out through field observations and closed questionnaires. The analysis technique in the research is simple linear regression analysis technique with product moment correlation test. The results of the study can be concluded that the price of tcount> ttable is 13.760> 1.663, then the hypothesis is stated H0 (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted, thus the hypothesis is stated that there is an influence of the Raskin Program on improving the welfare of poor families in Pagadungan Village, Karangtanjung District, Pandeglang Regency, with a correlation value of r = 0.837 which means that the level of influence of the Raskin Program on improving the welfare of poor families is interpreted to have a very strong relationship. Determination correlation of 0.700 which means that the influence of Raskin distribution programme can affect the welfare of poor families 70%, while the remaining 30% is caused by other factors.